The church and cultures : new perspectives in missiological anthropology - Luzbetak, Louis J. (Maryknoll, N.Y. : Orbis Books, 1988)
Bibliography: p. 411-452. Includes index.
Keywords: Missions -- Anthropological aspects; Christianity and culture